EVALUASI KINERJA KEUANGAN UNTUK PENGENDALIAN MANAJEMEN PADA PERUM PEGADAIAN - Adam Salehe (AkMen JURNAL ILMIAH, 2009)
This Research aim to to know and evaluate the finance performance and its role in financial control by management of Perum of Pawnship Office Branch the Antang. This Research use the approach deskriptif-kuantitatif with the historical data bases. measurement of finance Performance focussed at expense element. Is hereinafter done conducted by analysis varians intended to be careful of deviation from budget goals which have been specified with its realization. Result of research indicate that the budget goals not yet as according to its realization, especially at expense post which is there are a lot of varians which unfavorable, so that forwards, require to be controlled by management, whereas in ratio analysis finance, indicating that from three analysed finance ratio, that is ratio of officer expense to earnings, ratio of administration expense to earnings, and ratio of general expense to operating income, altogether show the ratio number exceeding permitted ratio standard